Does Antibiotic Therapy Affect Time to Clearance in Post-Active Phase Streptococcal Guttate Psoriasis—A Case Control Study. Issue 1 (January 2021) - Farrell, Joshua; Stewart, Thomas Jonathan; Rosen, Robert Howard
Background: The extent of the role of streptococcal infection in the pathogenesis of guttate psoriasis is still unclear. Data on the efficacy of antibiotic therapy in guttate psoriasis is limited, heterogeneous and conflicting. Objective: We sought to ascertain whether single-course oral antibiotic therapy affects time to skin clearance in acute post-active phase streptococcal guttate psoriasis. Methods: We performed a 5-year case-control study of ASOT-positive guttate psoriasis treated with or without single-course oral antibiotic therapy with 8-week follow-up. Results: There was no significant difference between cases and controls for time to clearance (χ 2 = 0.92, p = 0.82). Conclusion: Our findings suggest that single-course oral antibiotic therapy may not provide any adjunctive therapeutic benefit in the treatment of acute post-active phase streptococcal guttate psoriasis.